2005
DOI: 10.2337/diacare.28.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Variables at Low Levels in Childhood Are Beneficially Associated With Adulthood Cardiovascular Risk

Abstract: OBJECTIVE -Most epidemiologic studies have focused on the adverse impact of the metabolic syndrome on cardiovascular (CV) disease. However, information on the relationship between the clustering of metabolic syndrome variables at favorable levels in childhood and the measures of CV risk in adulthood is not known. RESEARCH DESIGN AND METHODS -The study cohort included 1,474 individuals (552 blacks and 922 whites) who were examined for CV risk factors in childhood (aged 4 -17 years) and again in adulthood (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 38 publications
1
89
1
7
Order By: Relevance
“…Such risk factors are usually found in constellation with obesity and insulin resistance underlying conditions of hypertension, thrombosis and dyslipidaemia among others. 53 Furthermore, the constellation of metabolic syndrome variables at low levels in childhood is associated with a lower measure of cardiovascular risk in adulthood. 54 Kemper 55 has shown that less intake of salt reduces the BP level.…”
Section: Discussionmentioning
confidence: 99%
“…Such risk factors are usually found in constellation with obesity and insulin resistance underlying conditions of hypertension, thrombosis and dyslipidaemia among others. 53 Furthermore, the constellation of metabolic syndrome variables at low levels in childhood is associated with a lower measure of cardiovascular risk in adulthood. 54 Kemper 55 has shown that less intake of salt reduces the BP level.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the current pediatric literature on the MS, it is difficult to find long-term epidemiological studies that have all the required information, and the maximum duration of follow-up is not long enough. 61,62 Only Rodriguez-Moran and co-workers 25 looked at the genetic background derived from the children's family history (i.e., phenotype and genotype). Knowledge of the presence of obesity-related diseases in the family is as important for the estimation of cardiovascular risk as the evidence of metabolic abnormalities.…”
Section: Major Concernsmentioning
confidence: 99%
“…1,2 Patterns of cardiovascular risk factors in populations are not static over time and they are associated with changes in the pattern of cardiovascular disease. 3,4 Overweight in adolescents has become a major public health concern in the United States and throughout the world. 5,6 Fewer data are available on blood pressure trends in youth.…”
Section: Introductionmentioning
confidence: 99%